Factors Affecting Financing at Panin Dubai Syariah Bank: 2014-2022 - Azizah, Salsabila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This article investigates the influence of the CAR, TPF, NPF, return on assets (ROA), and BI Rate on financing at Bank Panin Dubai Syariah. Internal quantitative data used in this study were obtained from quarterly financial reports in the period of 2014 - 2022, while external data were obtained from BPS reports. The analysis method used was the Error Correction Model (ECM). In the long run, TPF and ROA variables have a positive influence on financing in Panin Dubai Syariah, while NPF and BI Rate variables have a negative influence. CAR variable does not have a long-term influence on financing in Panin Dubai Syariah. In the short term, only the ROA variable has a positive influence on financing in Panin Dubai Syariah. These four variables do not have a short-term influence on financing in Panin Dubai Syariah. The results of the study indicate that the performance of Panin Dubai Syariah as an intermediary institution in channeling financing to the public is stable in the long run, but in the short term, the bank experiences instability in the development of financing.